An analysis of financial and monetary asymmetries in the light of the experiences of Brazil and China - Teixeira Leal, Júlia (Brazilian Keynesian Review, 2025)
The analysis of financial asymmetry stems from the consequences of the end of the Bretton Woods agreement and the greater movement of capital between countries, as a result of financial globalization. Monetary asymmetry, on the other hand, stems from the existence of a hierarchy of currencies and this article intends to include the analysis of the internationalization process. The article aims to contribute to the debate by analyzing the impacts of these asymmetries on countries, using Brazil (due to its importance in Latin America) and China (due to its relevance in East Asia, in addition to being the second largest world economy) as case studies. The argument used is that Brazil is more affected by asymmetries due to the way it has inserted itself in financial globalization and the role that its currency plays at the international level. On the other hand, China, as a superpower of the Global South, has gradually inserted itself into financial globalization and has been promoting the expansion of the use of its currency internationally, being less affected by asymmetries.